The Influence of Online Learning Models and Learning Interests Toward Learning Outcomes of Lay Up Shoot Basketball - Alfian, Reza; Soegiyanto, Soegiyanto; Sulaiman, Sulaiman (Journal of Physical Education and Sports, 2021)
The appropriate learning model is the key to success. The purpose of the study was to analyze the effect of the Self Organized Learning Environment (SOLE) and Introduction Connection Application Reflection Extension (ICARE) learning models on lay-up basketball learning outcomes. Experimental research method with a 2x2 Factorial Design research design. The number of samples is 32 in class XI. The independent variables are the SOLE and ICARE learning models, the attribute variables being high and low interest in learning. The dependent variable is lay-up shoot basketball learning outcomes. The instrument is a test of attitudes, knowledge and skills. Data analysis used two way ANOVA. The results of the study: 1) the influence of the learning model is on the attitude aspect Fcount = 6.29>Ftable= 4.18/p = 0,018. Knowledge aspect Fcount=1.12 p=0,299 and skill aspect Fcount=1.32 < Ftable=4.18 p= 0,260. 2) there is no difference in the effect of the learning model on the attitude aspect Fcount=2.32 < Ftable=4.18 p=0,139, the knowledge aspect Fcount=3.02 < Ftable=4.18 p=0,093 and the skill aspect Fcount=3.45 < Ftable=4.1 p=0.073. 3) there is an interaction between the learning model that simultaneously influences students' learning interest in the attitude aspect Fcount = 40.00>Ftable = 4.18/p = 6,564. Knowledge aspect Fcount=3.10 < Ftable=4.18 p=0,089 and skill aspect Fcount=0.11< Ftable=4.18 p=0,743. Conclusion SOLE and ICARE learning models can increase students achieving lay-up shoot learning outcomes. The improvement shown by students is only in the attitude aspect of students who can work together with their friend.